Mapping Gestational Diabetes Mellitus – A Narrative Review of Key Determinants and Epidemiology - Sarfaraz, Sana; Rizwan, Nazia; Sharif, Amber; Altaf, Rabia; Nasim, Maaz Bin; Syed, Shahzada Khurram; Mushtaq, Atifa; Asim, Fahad; Mushtaq, Muhammad Naveed; Sarfraz, Muhammad; et al. (Biological and Clinical Sciences Research Journal, 2025)
Gestational diabetes mellitus (GDM) is a glucose intolerance disorder that arises during pregnancy, posing significant risks to both maternal and neonatal health. The global burden of GDM is increasing, reflecting changes in demographic, genetic, and lifestyle factors. Objective: This narrative review aims to explore the epidemiology, risk factors, diagnostic criteria, and current preventive and management strategies associated with GDM, with an emphasis on its public health implications. Methods: This review utilized a comprehensive literature search of international databases including PubMed, Scopus, and Google Scholar. Relevant articles published in English over the last ten years were included. Keywords such as “gestational diabetes,” “GDM risk factors,” “insulin resistance in pregnancy,” and “maternal outcomes” were used. Epidemiological trends, diagnostic approaches, and evidence-based prevention and treatment methods were synthesized from cohort studies, meta-analyses, and clinical guidelines. Results: The global prevalence of GDM varies significantly, ranging from 1% to 28%, largely influenced by screening protocols, lifestyle, and ethnic composition. Risk factors for GDM include maternal obesity, advanced maternal age, family history of diabetes, polycystic ovarian syndrome (PCOS), and ethnicity. The pathophysiology involves insulin resistance, exacerbated by placental hormones. Lifestyle interventions—particularly dietary modifications and physical activity—remain the cornerstone of management. Continuous glucose monitoring (CGM) and early screening contribute to improved glycemic control and better maternal-fetal outcomes. The link between GDM and future development of type 2 diabetes mellitus highlights the importance of postpartum follow-up. Conclusion: GDM is a growing public health concern due to rising obesity and type 2 diabetes rates. Early detection, individualized care plans, lifestyle interventions, and postpartum monitoring are critical to minimizing complications and improving long-term outcomes for both mothers and offspring.